PERAN VARIASI MENU, LOKASI, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN KEMBALI (STUDI KASUS PADA ZACTIE BAR AND RESTAURANT) - Ni Wayan Putri Findia Antika; Ni Luh Putu Indiani (Warmadewa Management and Business Journal (WMBJ), 2023)
In the midst of increasingly intense competition in the culinary industry marked by a significant growth in the number of restaurants in recent years, marketers need to put extra effort into understanding consumer needs and wants. A better understanding can be a reference in developing marketing strategies to increase consumer interest in repurchasing. This is the background of this study to analyze the factors that drive repurchase decisions. This study conducted a case study at Zactie Bar and Restaurant Denpasar. The population in this study are consumers who visit Zactie Bar and Restaurant. The research sample amounted to 96 respondents who were taken using the Crochran formula. The method of data collection is a survey with a questionnaire. Multiple linear regression analysis technique was used to test the effect of the independent variable on the dependent variable. The results of the study found that menu variations, location, and service quality had a positive and significant effect on purchasing decisions. In an effort to improve purchasing decisions, aspects that need to be considered regarding menu variations are increasing the types of food and beverage choices, creating unique and varied flavors of food and beverages and increasing the portion sizes of food and beverages. Aspects that need to be considered in site selection are the affordability of the location, smooth access to the location, and the proximity of the location to the center of community activities. Aspects that need to be considered in improving service quality are employee reliability, employee responsiveness, food quality assurance, understanding of consumer demand, and the comfort of the restaurant space.